Revitalizing Rare Angon: Fostering Loyalty, Innovation, Youth Unity, Sustainable Agriculture Strategy in Balinese Culture and Tradition - I Nengah Suardhana; I Putu Agus Santana; Anak Agung Ayu Ratih Kesumadewi; I Gusti Bagus Rai Utama (LITERA : Jurnal Bahasa Dan Sastra, 2026)
This study examines the transformation of Rare Angon traditions within the context of the Balinese kite festival, with particular attention to shifts in youth participation, cultural meaning, and innovation. The research adopts a mixed-methods approach using an explanatory sequential design, integrating quantitative survey data from 150 respondents with qualitative interviews, participant observation, and visual analysis. The findings indicate a significant generational shift in the interpretation of kite-flying practices. Older participants continue to uphold strong spiritual values grounded in Hindu cosmology, particularly the symbolic relationship between Shiva and Parvati. In contrast, younger participants increasingly view the festival as a platform for creativity, competition, and social interaction. This shift reflects a broader transformation from ritual-based devotion to performative cultural expression. Drawing on the Tri Hita Karana framework, the study demonstrates that the kite festival continues to maintain a dynamic balance among spiritual (parahyangan), social (pawongan), and environmental (palemahan) dimensions. At the same time, innovations in kite-making techniques and the integration of tourism-related elements have enhanced youth engagement, while also raising concerns regarding cultural commodification. The study concludes that the sustainability of Rare Angon traditions depends on the capacity to negotiate continuity and change through adaptive cultural practices. These findings contribute to broader discussions on cultural resilience, heritage transformation, and sustainable tourism in contemporary societies.